Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1080/02699052.2016.1183821
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of inpatient (neuro)rehabilitation after acute care of severe traumatic brain injury: An epidemiological study

Abstract: Patients' pathways after acute care are not only determined by the severity of their brain injury, but also by their overall injury severity and socio-biological factors. More than half of the patients after sTBI are not discharged to specialized inpatient neurorehabilitation and, therefore, efforts should be taken to optimize post-acute care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 25 publications
4
37
1
Order By: Relevance
“…Admission rates to neurorehabilitation for survivors of severe TBI differ widely between countries. Data from specialized trauma centres in Texas (U.S., 11 centres), Switzerland (12 centres), Norway (4 centres), and Denmark (4–5 centres) show rates of 45%, 44% (+16% non-specialized rehabilitation), 75% (+11% non-specialized), and 84%, respectively [76,77,78,79]. The comparability of these data is limited as a result of unequal populations (e.g., the Norwegian and Danish ones showing a notably lower mean age and a large proportion of younger patients, respectively), but these differences could also partly be explained by health system-inherent factors such as national guidelines, cost coverage/reimbursement, and centralization of institutions.…”
Section: Admission To Rehabilitation After Tbimentioning
confidence: 99%
“…Admission rates to neurorehabilitation for survivors of severe TBI differ widely between countries. Data from specialized trauma centres in Texas (U.S., 11 centres), Switzerland (12 centres), Norway (4 centres), and Denmark (4–5 centres) show rates of 45%, 44% (+16% non-specialized rehabilitation), 75% (+11% non-specialized), and 84%, respectively [76,77,78,79]. The comparability of these data is limited as a result of unequal populations (e.g., the Norwegian and Danish ones showing a notably lower mean age and a large proportion of younger patients, respectively), but these differences could also partly be explained by health system-inherent factors such as national guidelines, cost coverage/reimbursement, and centralization of institutions.…”
Section: Admission To Rehabilitation After Tbimentioning
confidence: 99%
“…Some studies have reported sex differences in service provision, such as higher healthcare use in females (15). In other studies, males received more services (16), or sex was not related to service provision (8,9). Furthermore, some studies reported that younger individuals with TBI more often received rehabilitation (8,(15)(16)(17), while others reported that older aged individuals received more rehabilitation services (16,18,19).…”
mentioning
confidence: 99%
“…4 12 During the last decade, improving quality of care and increasing the number of survivors have gradually shifted the focus of research from discharge status (morbidity or mortality) [22][23][24] to that of discharge destination. [25][26][27] In order to use discharge destination as a measure of clinical priorities and pathway of care, it is important to understand the factors that contribute to this outcome. While some studies suggest that discharge to a rehabilitation setting is mostly related to preinjury functioning and overall severity of injury, 25 27 28 others indicate that demographic and socio-economic factors are the main elements that correlate with discharge to rehabilitation facilities versus home and other institutionalised care settings.…”
mentioning
confidence: 99%